Experimental study of flows in a porous pipe - Lin, Wanxi (2015)
The Moody diagram is used extensively to determine friction resistance in wall bounded flows; it is well-cited and provides accurate information for impermeable-rough bounded flows. However it does not account for the effect of wall permeability. Thus, in practice the effect of permeability for flows through permeable-rough boundary pipes is often ignored for simplicity since information on such flows are limited and not easily assessable. Moreover, there has been an increasing interest in highly porous materials such as the catalytic converters where the mass transfer is a crucial factor. Presently, the mass and flow transfer in these porous materials are not fully understood. The application of mass and flow transfer also extends beyond the scope of environment transport such as the petrochemical industry. Nikuradse (1933), the founder to some of the most important concepts in fluid mechanics conducted experiments on rough walls with slight permeability made by one layer of sand. However, many geophysical flows occur in highly permeable channels, such as gravel-bed rivers where the roughness to depth ratio are of many orders larger. Studies on permeable-rough bounded flows done in the past are mainly conducted in open channels, where it is subjected to the effect of surface variance. In this study, to eliminate the surface disturbances and to better account for the head loss, the experiment was conducted with pipe flows. The experimental results obtained in the current project show that wall permeability has considerable effect on the friction resistance. Comparisons were also made with the Nikuradse’s observations.